Implementasi Penggunaan BPJS Kesehatan dalam Penanganan Balita Stunting di Lokus Stunting: Implementasi Penggunaan BPJS Kesehatan dalam Penanganan Balita Stunting di Lokus Stunting - Agustina, Rakhmawati; Weken, Merdekawati Evangli; Anggraeny, Dyta (Amerta Nutrition, 2023)
Background: Community-based health insurance is increasingly integrated into the Indonesia health system. Health protection is one of the dimensions in the Special Index for Stunting Management (IKPS). The Indonesia National Health Insurance, regulated by Social Health Insurance Administration (BPJS Health), has stunting handling programs. Stunting is less likely to occur in toddlers who have health insurance. Objectives: To explore the use of by BPJS Health for handling stunting in the stunting locus area. Methods: Qualitative research using a case study was conducted in the Wori Primary Health Service. Snowball sampling methods and recruit 9 participants: health service and village staff, a mother with a stunting toddler, and cadres. All interviews, were audio-recorded and transcribed verbatim. Thematic analysis was used to and using OpenCode software. Results: Even though there was local health insurance, the regional government kept supporting BPJS Health ownership for stunting toddlers. They get referral services to pediatricians for further screening, but this cannot be carried out due to the low ownership of by BPJS Health. The determining variables were the absence of a toddler's National Identity Number, the drawn-out procedure, and the mother's perception of the risk of stunting. Because of the lower knowledge barrier and accessibility to other healthcare facilities, they thought it was sufficient to treat stunting at the Primary Health Service level. Conclusions: The benefits of BPJS may be seen in the stunting handling program at the Wori Primary Health Service, however, there is a need for coordination of various components to inform it.